A study of association between presence or absence of GSTT1 and GSTM1 and/or single nucleotide polymorphism in FABP2 and GSTP1 with incidence of diabetes type 2: a case-control study - Hira Jamil; Adeela Awan; Atif Akbar; Muhammad Babar; Sana Akhtar; Rana Khalid Iqbal; Furhan Iqbal (Journal of the Pakistan Medical Association, 2022)
Objective: To assess the association of single nucleotide polymorphisms in fatty acid binding protein-2 (rs1799883) and glutathione S-transferase pi (rs1695) genes with presence/absence of glutathione S-transferase mu and glutathione S-transferase theta genes in type 2 diabetes. Methods: The cross-sectional case-control study was conducted at Institute of Molecular Biology and Biotechnology during March till September 2019 and comprised type 2 diabetes patients and non-diabetic controls from two districts in southern Punjab. Polymerase chain reaction, polymerase chain reaction-restriction fragment length polymorphism and tetra-primer amplification refractory mutation system-polymerase chain reaction were applied to investigate glutathione S-transferase theta, mu and pi genes as well as fatty acid binding protein-2, as appropriate. The association of single nucleotide polymorphisms in all genes with the disease were studied either individually or in various combinations. Data was analysed using Minitab 18. Results: Of the 448 subjects, 248(55.4%) were patients and 200(44.6%) were controls. Overall there were 213(47.5%) males and 235(52.5) were females, and 141(31.5%) were aged 30-46 years. The presence of rs1799883 in fatty acid binding protein-2 (p=0.03) and the absence of glutathione S-transferase mu gene (p<0.001) had significant association with type 2 diabetes, while the presence of glutathione S-transferase theta and rs1695 in glutathione S-transferase pi genes were not associated with the disease. Individuals with glutathione S-transferase mu gene null and Ileu/Ileu or Ileu/Val genotype of rs1695 in glutathione S-transferase pi gene have potential to develop type 2 diabetes in their lifetime (p<0.05). —Continue